EVALUATION OF FINANCIAL PERFORMANCE OF NATIONAL OIL & GAS COMPANIES IN SOUTHEAST ASIA (CASE STUDIES OF PERTAMINA - INDONESIA, PETRONAS - MALAYSIA, AND PTT - THAILAND) - WIBISONO (NIM 29114039), IMAN
The oil and gas industry contributes greatly to the global economy, especially to the economies of oil and gas producing countries. The National Oil and Gas Company, not only contributes to the oil-producing country's economy, but also to maintain national energy security. However, the oil and gas industry is declining. Since mid 2014, oil prices have dropped dramatically to almost 50% and have an impact on the performance of oil and gas companies. The objective of this study was to evaluate the financial performance of three National Oil & Gas Companies in Southeast Asia (Pertamina, Petronas and PTT) in the period 2011 to 2016 and to confirm financial performance and performance efficiency with industry benchmarks and Data Envelopment Analysis (DEA). The data is measured based on secondary data from published annual report and financial report from 2011 to 2016. The research methodology used is financial ratios categorized into: liquidity (current ratio, quick ratio and cash ratio), solvency (debt to equity, debt to assets and interest coverage ratio), activity (inventory turnover, account receivable, fixed asset turnover, and total asset turnover), and profitability (return on asset, return on equity, gross profit margin, and net profit margin). Comparison with industry benchmarks and Data Envelopment Analysis (DEA), is used to confirm the financial performance and the performance efficiency of related firms. The study have shown that of the three National Oil and Gas Companies, Petronas shows the most outstanding financial performance. Pertamina's financial performance is moderate and PTT's at the lowest performance. Confirmation uses comparisons with industry benchmark, revealing that all NOCs overall financial performance are above industry benchmark. However, confirmation using DEA, shows that the most superior performance efficiency is in Pertamina, followed by PTT and the lowest is Petronas.